Специфіка саморегуляції особистості у працівників різних відділів митниці - Іванченко, Ю. С.; Ivanchenko, Yu. S. (Вісник Національного університету оборони України. - 2014. - Вип. 1(38). - С. 219-223, 2014)
У статті висвітлено результати дослідження особливостей процесів саморегуляції особистості працівників вантажного і пасажирського відділів митниці. Визначено, що рівень вольової саморегуляції у професійно успішних митників вантажного відділу вищий ніж у їх колег з пасажирського відділу . Діагностовано, що поведінкова активність працівників митниці обох відділів раціональна, обережна, помірно активна. З’ясовані відмінності властивостей «предметно-орієнтовного» і «комунікативного» аспектів темпераменту митників вантажного і пасажирського відділів.

The results of research of features of processes of self-regulation of personality of workers of freight and passenger departments of custom are reflected in the article. Certainly, that the level of volitional self-regulation for the professionally successful customs officials of freight department is higher than for their colleagues from a passenger department. The customs officials of freight department with low professional success require social contacts and aspire to leadership and employment of high grade. Professionally the successful customs officials of freight department have a wide set of the communicative programs and switching lightness in the process of communication. Customs officials with low professional success of passenger department are sensible to the estimations of surrounding people and failures in a communication. Professionally the successful customs officials of passenger department have speed descriptions of lingually-motive acts in the process of communication, lightness of switching of attention from one man on other in the process of communication.

В статье отражены результаты исследования особенностей процессов саморегуляции личности работников грузового и пассажирского отделов таможни. Определено, что уровень волевой саморегуляции в профессионально успешных таможенников грузового отдела выше, чем у их коллег из пассажирского отдела. Диагностировано, что поведенческая активность работников таможни обоих отделов рациональна, осторожна, умеренно активна. Выяснены различия свойств «предметно-ориентированного» и «коммуникативного» аспектов темперамента таможенников грузового и пассажирского отделов.
Features of self-regulation of personality of workers of different departments of custom
Keywords: працівники митниці; customs officials; работники таможни; саморегуляція; self-regulation; саморегуляция; професійна діяльність; professional activity; профессиональная деятельность; вольова саморегуляція; volitional self-regulation; волевая саморегуляция; темперамент; temperament